INFLAMMATORY MARKERS IN END-STAGE RENAL DISEASE PATIENTS ON HAEMODIALYSIS - Abdel-Messeih, Phebe Lotfy; Alkady, Manal Mohamed; Nosseir, Neveen Mostafa; Tawfik, Mohamed Said (Journal of Medical Biochemistry, 2020)
Background: CXC chemokine ligand 16 (CXCL16) is an inflammatory chemokine that mediates renal infiltration of macrophages and activated T cells.Aim: To investigate serum levels of CXCL16 in patients undergoing hemodialysis and their correlation with other inflammatory markers such as C-reactive protein (CRP) and intact parathyroid hormone (iPTH).Methods: The study included 40 hemodialysis patients (22 males) and 40 age and gender-matched controls (24 males). Fasting blood sugar (FBS), urea, creatinine, calcium and inorganic phosphorous were assayed in participants using routine methods, glycosylated hemoglobin (HbA1c) by quantitative chromatographic spectrophoto metry, iPTH by chemiluminescent microparticle immuno assay, CRP by nephelometry and CXCL16 by ELISA technique.Results: Serum CXCL16, CRP, PTH, FBS, urea, and creatinine levels were significantly higher in hemodialysis patients compared to controls (p
Keywords: CXCL16, iPTH, CRP, ESRD